Coronary Suture Size Difference Analysis Between Conventional Methods and Morphometric Methods During Ventriculo Peritoneal Shunt Operation - Jefri Henky (Sean Institute, 2023)
Placement of a ventricular catheter in a VP shunt or EVD is a very important life saving measure, done correctly, safely and quickly. This action needs attention because the components of the ventricular catheter are considered as the most common cause of mechanical failure in cases of shunt malfunction. The characteristics of the research variables will be presented in the form of concentration values and data variations, while the bivariate data will be analyzed using the t test to analyze the difference in the average coronary suture distance determined using the conventional method and the morphometric method. Significance was determined based on the p-value which was ≤ 0.05 and a confidence interval (CI) of 95%. An observational study was carried out in the operating room of Semen Padang Hospital in hydrocephalus patients who had a VP shunt installed, a sample of 40 patients was collected, then analyzed computerized to present the characteristics of the research subjects. The mean age of patients who underwent VP shunt installation was 46.13 + 125 years. The mean size of the patient's head circumference was 55.60 + 1.297 cm, while the average size of the patient's nasion-POE anatomy was 33.38 + 1.030 cm. The mean thickness of the patient's scalp was 7.73 + 0.679 mm. The average size of the coronary suture anatomy from the patient's orbital rim is 11.81 + 0.443 cm, with a difference in the measurement accuracy of conventional suture identification which is 8.13 +4,43 mm. Meanwhile, the mean difference in size accuracy of morphometric identification of sutures was 6.63 + 6.18 mm. The variable size of the patient's head circumference was normally distributed (p = 0.077), the anatomical size variable of the nasion-POE was normally distributed (p = 0.061), the variable size for scalp thickness was also normally distributed (p = 0.102), the variable size of the coronary suture of the orbital rim was distributed was normal (p = 0.072), the variable difference in the accuracy of the conventional method of identification was normally distributed (p = 0.114) and the difference in the measure of the accuracy of the identification of the morphometric method was also normally distributed (p = 0.084). The difference in mean coronary suture identification size between the conventional method and the morphometric method was 1.475 + 0.107 cm, meaning that there was a significant difference in the mean coronary suture identification size between the conventional method and the morphometric method with a p value <0.001. The mean difference in the difference in the size of the coronary suture identification between the conventional method and the morphometric method was 1.500 + 1.202 mm, meaning that there was a significant difference in the mean difference in the size of the coronary suture identification between the conventional method and the morphometric method with a p value <0.05. The morphometric method in identifying coronary sutures has a greater percentage of accuracy and is closer to the actual size of the coronary sutures.